2004
DOI: 10.1111/j.1600-0749.2004.00141.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of HLA Class I Antigens and HLA Class II Alleles with Vitiligo in a Turkish Population

Abstract: As is the case with many other autoimmune diseases, there is an association between vitiligo and HLA complex. HLA subtypes vary with racial/ethnic background. The purpose of this study was to determine which HLA class I antigens and HLA class II alleles are associated with Turkish vitiligo patients. Forty-one patients with vitiligo and 61 healthy control subjects were typed for HLA class II alleles. Thirty-three out of 41 patients with vitiligo and 100 healthy transplant donors were typed for HLA class I antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 19 publications
5
50
0
1
Order By: Relevance
“…The study of major histocompatibility complex genes has revealed associations of vitiligo with certain human leukocyte antigens. 16,17 Polymorphic markers in the CTLA-4 gene that are associated with autoimmunity are also associated with vitiligo that occurs with other autoimmune disorders. [10][11][12] Vitiligo can also develop as 36 Likewise, the autoimmune susceptibility loci AIS1, AIS2 and SLEV1 are associated with generalised vitiligo that occurs with other autoimmune conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of major histocompatibility complex genes has revealed associations of vitiligo with certain human leukocyte antigens. 16,17 Polymorphic markers in the CTLA-4 gene that are associated with autoimmunity are also associated with vitiligo that occurs with other autoimmune disorders. [10][11][12] Vitiligo can also develop as 36 Likewise, the autoimmune susceptibility loci AIS1, AIS2 and SLEV1 are associated with generalised vitiligo that occurs with other autoimmune conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Furthermore, several genes that have a role in regulating immunity have been associated with susceptibility to vitiligo including: polymorphic markers in the cytotoxic T lymphocyte antigen-4 (CTLA-4) gene, the autoimmune susceptibility loci AIS1, AIS2, AIS3 and SLEV1 and certain human leukocyte antigen specificities of the major histocompatibility complex. [10][11][12][13][14][15][16][17] Recently, the missense R620W polymorphism in the PTPN22 gene at nucleotide 1858 (1858C-T) in codon 620 (620Arg-Trp) has been associated with autoimmune diseases including type I diabetes mellitus, Graves' disease, systemic lupus erythematosus and rheumatoid arthritis. [18][19][20][21][22][23][24][25] The gene, located on chromosome 1p13, 19 encodes lymphoid protein tyrosine phosphatase (LYP), which is important in the negative control of T lymphocyte activation.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Briefly, DNA extraction was carried out by classical phenol-chloroform method from fresh whole blood samples which were anti-coagulated by ethylene diamine tetra acetate. The PCR sequence specific primer (PCR ⁄ SSP) method was used to determine HLA DNA typing.…”
Section: Methodsmentioning
confidence: 99%
“…17 Because of HLA gene polymorphism, the results of these reports may vary according to the population studied. 18 A high incidence of HLA-DRw12 and -A2 antigens was detected in a population of Caucasian Germans. 19 Hungary, Poloy et al showed the association with HLA-DR1.…”
Section: Vitiligomentioning
confidence: 99%
“…23 In Turkey, HLA-DRB1*03, -DRB1*04 and -DRB1*07 alleles were considered risk markers. 18 Other researches showed differences in the association of HLA and vitiligo in terms of age at onset, presence of family history and clinical manifestations. HLA-DR4 antigen is more frequent in individuals with early manifestation (less than 20 years old), while HLA-DRw6 antigen is associated with late development.…”
Section: Vitiligomentioning
confidence: 99%